Convergence of European transition economies and the EU: What do the data show - Vadims Sarajevs (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This is an empirical study of the real income convergence among the fifteen European Union members and the eleven transition economies of Central and Eastern Europe.Debates and research on EU enlargement tends to concentrate on normative issues, so empirical studies constitute a small share of published work on the subject. This empirical investigation relies on available data on transition, and employs several econometric techniques including graphic analysis, classical cross-section regression and dynamic panel data estimations.Most estimation methods find positive convergence, but estimated rates of convergence vary considerably.
URN:NBN:fi:bof-201408071952
Keywords: 330